Carcinoma arising within sciatic nerve endometriosis: a case report. Issue 12 (11th December 2021) - Yahaya, Adaiah; Chauhan, Govind; Idowu, Adeyemi; Sumathi, Vaiyapuri; Botchu, Rajesh; Evans, Scott
Abstract: Endometriosis is a common condition with significant morbidity. There have been case reports of endometrial deposits affecting the sciatic nerve. Sciatic nerve endometriosis presents with cyclical sciatica and is often difficult to diagnose as it mimics many other causes of sciatica. We report the first case of histological proven endometrial carcinoma arising in a pre-existing sciatic nerve endometriosis. This was initially managed with radiotherapy however symptoms persisted and she opted to have surgery with the aim of better symptom control and long-term prognosis.